MULTICULTURAL TEACHING IN EFL CLASSROOM - Yulieda Hermaniar; Tri Winindyasari Palupi; Yasyir Fahmi Mubaraq (UMBanjarmasin, 2021)
Multiculturalism is the identity of most schools in Indonesia since the term deals with varieties in students’ cultural backgrounds. In today’s curriculum, multiculturalism is stated explicitly in an attempt to promote character buildings. As the result, the teaching and learning process should highlight the aspect of multiculturalism in material, media, as well as teaching strategies. In the implementation, there are some challenges faced by the English teachers. Therefore, the purpose of this study is to describe issues faced by teachers in highlighting multiculturalism value to the teaching of English in a vocational school in Kalimantan Selatan. Four schools are taken as the subject of the study. They are SMKN 4 Banjarmasin, SMKN 3 Banjarbaru, SMKN 1 Bati-Bati, and SMKN 1 Tapin Selatan. Interview and observation are conducted to gather the data that is presented descriptively by following Cresswell’s stages; data transcribing, coding and data classification, data interpretation, and drawing the conclusion. The result of the study concludes the challenges faced by the teachers to highlight the multiculturalism aspect in the classroom. The challenges are in terms of media, material, teaching strategies, and support.